Ocorrência e caracterização morfológica e química de microplásticos na costa da cidade de Fortaleza (Ceará, Brasil) - Banegas, Maria Elena Nolasco (2021)
Microplastics (MPs) are partic les and fibers of synthetic polymers from 1 µm to 5 mm in size that have different compositions and chemical structures MPs are pollutants of global concern because they are present in the main marine environments o n Earth. This work objective is to evalu ate the occurrence and characterize morphologically and chemically of MPs in ocean waters samples from the coast of Fortaleza city (CE) by visual identification and quantification through a stereoscopic microscope and chemical identification of the particl es by i nfrared and Raman spectroscopy in addition to differential scanning calorimetry . The water samples were collected with a Neuston sampler, with 100 µm mesh size. Then, they were dried in an oven at 90º C and 35 % hydrogen peroxide (H 2 O 2 ) was added to oxidiz e the present organic matter . After the addition of a sodium chloride solution and a minimum rest of 24 hours , the separation of the MPs took place by density difference. The material was filtered through a nylon mesh with 65 µm of size and, after d rying a t room temperature, it was morphologically characterized by stereoscopic microscope . After that , chemical characterization was performed by Fourier transform infrared (FTIR) and Raman spectroscopy . The presence of M P s with varied morphologies was co nfirmed , in the form of fragments, fibers, foam and lamina in 9 different colors, with green, transparent and blue fibers and blue fragments being the most abundant. The sizes ranged from 4 µm to 5 mm. By comparing the FTIR and Raman spectra with reference polyme rs from the Wiley's KnowItAll Software database, the presence of polyurethane (PU) and alkyd resin, polyethylene (PE), polypropylene (PP), polystyrene (PS), blends of EPDM polyamide (EPDM PA), polyamide cellulose blend, thermoplastic rubber and poly ester f ibers was confirmed . Thus, it concludes that PE, PP, PA e PS enter the marine environment mainly through food packaging waste, polyester fibers through domestic sewage polluted with fibers from washing clothes, PU resin and alkyd resin through the w ear of surface coating of vessels, road markings and buildings, as well as thermoplastic rubber particles because of wear on car tires. Therefore, it is possible to infer that the main sources of MPs input in the marine environment of the Fortaleza coast is the a nthropic activities such as recreation, navigation/fishing and domestic activities. However , more exhaustive research is still needed to establish effective containment measures against contamination by MPs.